Timing of extreme drought modifies reproductive output in semi‐natural grassland. (1st January 2016) - Zeiter, Michaela; Schärrer, Sara; Zweifel, Roman; Newbery, David M.; Stampfli, Andreas
Abstract: Questions: Do extreme dry spells in late summer or in spring affect abundance and species composition of the reproductive shoots and the seed rain in the next annual crop? Are drought effects on reproductive shoots related to the rooting depths of species? Location: Species‐rich semi‐natural grassland at Negrentino, Switzerland. Methods: In plots under automated rain‐out shelters, rainwater was added to simulate normal conditions and compare them with two experimentally effected long dry spells, in late summer (2004) and in the following spring (2005). For 28 plots, numbers of reproductive shoots per species were counted in 1‐m 2 areas and seed rain was estimated using nine sticky traps of 102 cm 2 after dry spells. Results: The two extreme dry spells in late summer and spring were similar in length and their probability of recurrence. They independently reduced the subsequent reproductive output of the community, while their seasonal timing modified its species composition. Compared to drought in spring, drought in late summer reduced soil moisture more and reduced the number of reproductive shoots of more species. The negative effects of summer drought decreased with species' rooting depth. The shallow‐rooted graminoids showed a consistent susceptibility to summer drought, while legumes and other forbs showed more varied responses to both droughts. Spring drought strongly reduced density (–53%) and species richness (–43%) of the community seed rain, while summer drought had only a marginally significant impact on seed density of graminoids (–44%). Reductions in seed number per shoot vs reproductive shoot density distinguished the impacts of drought with respect to its seasonal timing. Conclusion: The essentially negative impact of drought in different seasons on reproductive output suggests that more frequent dry spells could contribute to local plant diversity loss by aggravating seed deficiency in species‐rich grassland. Abstract : We added rainwater to simulate normal conditions and compare them with experimentally affected extreme droughts in late‐summer and spring. Droughts strongly and independently reduced the subsequent seed rain and number of reproductive‐shoot. Drought timing modified the species composition of the reproductive output. The negative effects of summer drought on reproductive shoot density decreased with species' rooting depth.